2022
DOI: 10.1080/17435390.2022.2041756
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxic effects of metal-based nanoparticles in fish and bivalves

Abstract: There is a global research interest in metal nanoparticles (MNPs) due to their diverse applications, rapidly increasing use, and increased presence in the aquatic environment. Currently, most MNPs in the environment are at levels unlikely to cause overt toxicity. Sub-lethal effects that MNPs may induce, notable immunotoxicity, could however have significant health implications. Thus, deciphering the immunological interactions of MNPs with aquatic organisms constitutes a much-needed area of research. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 205 publications
0
13
0
Order By: Relevance
“…In another study, Mansour et al reported a decrease in total protein and globulin in Nile tilapia (Oreochromis niloticus) after 28-day exposure to AgNPs (Mansour et al, 2021). Previous studies demonstrated that nano metal base particles such as AgNPs can in uence the immune system via direct and indirect pathways (Fadeel, 2012;Rastgar et al, 2022). These particles can apply direct cytotoxic actions on the immune cells and changes in the immune system reactions such as the production of immune proteins, or these nanoparticles can directly interact with immune proteins such as the complement factors (Rastgar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Mansour et al reported a decrease in total protein and globulin in Nile tilapia (Oreochromis niloticus) after 28-day exposure to AgNPs (Mansour et al, 2021). Previous studies demonstrated that nano metal base particles such as AgNPs can in uence the immune system via direct and indirect pathways (Fadeel, 2012;Rastgar et al, 2022). These particles can apply direct cytotoxic actions on the immune cells and changes in the immune system reactions such as the production of immune proteins, or these nanoparticles can directly interact with immune proteins such as the complement factors (Rastgar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that nano metal base particles such as AgNPs can in uence the immune system via direct and indirect pathways (Fadeel, 2012;Rastgar et al, 2022). These particles can apply direct cytotoxic actions on the immune cells and changes in the immune system reactions such as the production of immune proteins, or these nanoparticles can directly interact with immune proteins such as the complement factors (Rastgar et al, 2022). Sulfurcontaining macromolecules such as proteins have a strong a nity for both ionic and nano-form of silver (Linhua et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Council for the Exploration of the Sea (ICES) concluded that almost all known chemicals seem to impact the immune system of fishes ( 34 ). Also nanoparticles are known to interfere with fish immunity [for review see ( 35 )]. Immune disturbances have been observed worldwide in fish populations living in contaminated habitats [e.g., ( 36 40 )].…”
Section: Immunotoxicology Has Relevance For the Health Of Fish Popula...mentioning
confidence: 99%
“…Much more extensive is the existing literature considering the formation of the endogenous corona. Endogenous corona determined biological identity of the NPs significantly modulates the cellular uptake, biodistribution of NPs (Treuel et al, 2013) and toxicity outcome in invertebrates (Lynch and Dawson, 2008;Nel et al, 2009;Docter et al, 2015; Frontiers in Toxicology frontiersin.org Durán et al, 2015;Zimmermann et al, 2017;Rastgar et al, 2022). For example the implication of NPs biomolecular corona in the immune response is also emerged in invertebrate models such as D. magna, M. galloprovincialis, and P. lividus (Wheeler et al, 2021).…”
Section: Endogenous Biomolecular Corona Formation In Invertebratesmentioning
confidence: 99%